Potential of Longan Seed Extract–Loaded Alginate–Chitosan Beads as Drug Delivery System - Buntum, Tanawat; Kakumyan, Pattana; Surassmo, Suvimol; Thanomsilp, Chuleeporn; Suwantong, Orawan (Frontiers in Materials, 2022)
The potential of a drug delivery system of the longan seed extract (LSE) incorporated in the alginate/chitosan (Alg/CS) beads has been studied. The LSE-loaded Alg/CS beads were prepared using the ionic gelation method via the interaction between protonated amino groups of CS and negatively charged carboxylic groups of Alg. Properties of the LSE-loaded Alg/CS beads were investigated including the morphology of the beads, particle sizes, encapsulation efficiency (%EE), controlled release profile, cytotoxicity, and biocompatibility. From the results, the amount of gallic acid, ellagic acid, and corilagin found in LSE was 25.61 ± 0.48,18.83 ± 3.75, and 21.92 ± 1.42 mg/g (based on the weight of LSE), respectively. The half-maximum inhibitory concentration (IC50) of LSE was 24.29 ± 1.08 μg/ml. SEM images of the LSE-loaded Alg/CS beads showed spherical shapes and rough surfaces with some aggregation. The particle sizes were between 1.9 and 2.5 µm with the PDI values of 0.1503–0.3183. Encapsulation efficiencies were between 11 and 18%. The released amount of LSE from the LSE-loaded Alg/CS beads was ranging between 68 and 93%. Moreover, cytotoxicity and biocompatibility tests showed that the beads were non-toxic to both NCTC clone 929 and NHDF cells and promoted the attachment of NHDF cells. Thus, these beads could be used as polymeric drug carriers.